Sexting in Singapore : psychosocial risk and protective factors - Low, Joey (2017)
Sexting is a neologism made up by the words “sex” and “texting” and it involves the sharing of sexually explicit photos and messages via mobile phone or the Internet. This study attempted to investigate the sexting behaviours in Singapore and explored possible psychosocial risk and protective factors associated with sexting. 205 participants (62 males and 143 females) were recruited for this study using convenience sampling and they were required to answer a series of questionnaires via the Qualtrics survey platform. Results showed that 113 participants (55%) reported receiving at least one sext while 72 participants (35%) have engaged in some form of sexting. These findings suggested that sexting is not an uncommon behaviour in Singapore. Additionally, histrionic personality, sensation seeking and positive attitudes toward sexting were found to be positively associated with intention to sext and actual sexting behaviours. This study suggested sexting is commonly used in Singapore and there are various psychosocial risk factors that may contribute to understanding the behaviour. Further research should be conducted on sexting to gain a better understanding of this potentially harmful phenomenon.